Electrical Resistivity Tomography in Geotechnical Engineering Applications - Sagar D.; Dwivedi S.B.; Basudhar P.K. (My University, 2025)
Characterization of subsurface soil is essential for foundation design of important civil engineering structures. In conventional geotechnical investigation, the soil profiling and their characterization are done by collecting samples from the field either through open pit sampling or through boring and then performing laboratory test for their classification and determination of strength and compressibility characteristics. In-situ methods like standard penetration test (SPT), cone penetration test, e.g., static (SCPT) and dynamic (DCPT), pressure meter test (PMT), and dilatometer test (DMT) are also available. But these methods are time consuming and costly. If vast tracts are to be investigated for preliminary exploration, then geophysical methods can aid to collect information about the subsoil conditions. Geophysical methods allow to measure physical properties like electrical resistivity, seismic wave velocity, electrical permittivity, magnetic intensity, etc. These observations can be used for surveying large tracts or ancient structures composed of dissimilar materials. Apart from these, some problems that vex the civil engineers is significant increase in the permeability of desiccated soils due to cracks in these soils due to shrinkage. Such a situation may lead to the progressive failure in flood embankments. Geophysical methods have great potential to aid archeological investigation in identifying archeological features in unexcavated areas. Electrical resistivity tomography (ERT) is very commonly applied in such studies because of its adaptability in identifying walls, cavities, etc., at different depths. The paper pertains to the potential of application of ERT in geotechnical and archeological investigation providing an overview and its use in subsoil profiling and detection of foundation details of old structures. The power of the method in identifying the hidden features of buried objects and subsurface profiling has been demonstrated with examples. © 2021, Springer Nature Singapore Pte Ltd.